Światło w poezji modernistów. ŚWIATŁOWSTĄPIENIE Tymoteusza Karpowicza i fragmenty The Pisan Cantos Ezry Pounda - Górniak, Karolina (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The aim of this article was to present a comparative interpretation of the selected poems by Tymoteusz Karpowicz (the poem alfaŚWIATŁOWSTĄPIENIE and a few accompanying poems) and Ezra Pound (The Cantos: LXXX, LXXXI and LXXXIII). The texts have been selected because of the theme of light, sun and visual perception. The comparative method is supposed to show 20th-century Polish poetry in the context of Anglo-American modernism. The relationship between the two poets seems to be hypothetical and one-sided. It has not been established so far whether the writings of Karpowicz were inspired by Pound’s texts. Thus, the article realized a model of contactless, comparative literary study, where comparisons are made on the basis of a typologic relationship. The first part of the article presented the theme of light in some non-poetic texts by Karpowicz and Pound and in their conception of art. The next two parts focus on the interpretation of poetry. The last chapter contained the conclusions drawn from the comparative analysis of chosen texts. The motif of light became not only a link between the selected poems, but also a reason for the comparison of the poetical techniques, specificity of style and the functions of linguistic experiments. The philosophical, Biblical, literary and even scientific contexts were evoked. A theoretical background was represented by the notion of reading/interpretation by Wolfgang Iser, transtextuality by Gérard Genette and the category of a model reader by Umberto Eco. The literary projects of Karpowicz and Pound impel readers to consider several issues. The most significant are: the limits of interpretation, obscurity or inexplicability of modern poetry and the problems of literary communication.